Workload and Performance of Auxiliary Nurse and Midwives at Selected Health Care Settings in North India - Salve, Anup D.; Mrs.Kavita; Singh, Amarjeet; Saini, Sushma K. (Universiti Kebangsaan Malaysia, 2015)
Introduction: Auxiliary Nurse Midwives (ANMs) are the back bone of primary health care services in India. The horizontal integration of various national health programmes has increased their responsibility and workload. So a need was felt to conduct a study to assess the workload and performance of ANMs. The objective of the study was to explore the workload and performance of ANMs in selected health care settings in North India. An exploratory crosssectional study was conducted in two selected health care settings of North India. Methods: The study was conducted on all the 7 ANMs working in the selected health care settings. Data was collected by observing the activities of ANMs using time activity record sheet. The nursing care procedures performed were observed and scored by using performance check list. T-test was used to compare actual time against standard time for performing procedures. Results: ANMs spent 2/3rd of their time in indirect care activities. Direct care and personal activities accounted for 19 % of their time. Their performance was rated as good. Conclusions: Majority of the time spent by ANMs was utilized in performing indirect care activities. This study recommends that more time is needed to be devoted to direct care by ANMs.